2010
DOI: 10.1093/alcalc/agq005
|View full text |Cite
|
Sign up to set email alerts
|

Initial Preference for Drinking Goal in the Treatment of Alcohol Problems: II. Treatment Outcomes

Abstract: The client's personal drinking goals should be discussed in assessment at treatment entry and as a basis for negotiation. Clinicians should be prepared to identify and support goal change as an unexceptional part of the treatment process that need not jeopardize good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
3
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 24 publications
10
79
3
4
Order By: Relevance
“…Consistent with previous studies (e.g., Adamson et al, 2010;Hodgins, Leigh, Milne, & Gerrish, 1997;Meyer, Wapp, Strik, & Moggi, 2014), clients with at-risk alcohol consumption choosing abstinence showed higher rates of successful treatment outcomes at both follow-up assessments. This difference also remained significant, when controlling for baseline differences between the two goal groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies (e.g., Adamson et al, 2010;Hodgins, Leigh, Milne, & Gerrish, 1997;Meyer, Wapp, Strik, & Moggi, 2014), clients with at-risk alcohol consumption choosing abstinence showed higher rates of successful treatment outcomes at both follow-up assessments. This difference also remained significant, when controlling for baseline differences between the two goal groups.…”
Section: Discussionsupporting
confidence: 89%
“…Substantial reductions in alcohol consumption were achieved in both intervention approaches. However, the patients maintaining abstinence for a longer time period only contributed marginally to this effect (Adamson, Heather, Morton, & Raistrick, 2010;Heather, Adamson, Raistrick, & Slegg, 2010). Furthermore, clients preferring abstinence differed from clients who expressed a preference for non-abstinence.…”
Section: Introductionmentioning
confidence: 95%
“…In other studies of alcohol-dependent or alcohol-abusing individuals, mostly in alcohol treatment settings but also in primary care-only settings, investigators found associations between a drinking goal of abstinence and improved alcohol use outcomes. [13][14][15][16][17] Finally, although not in a purely primary care setting, a trajectory-based investigation of alcohol use before treatment assignment among alcohol-dependent individuals revealed that very frequent drinkers, defined as a 75% probability of any alcohol use on a given day, benefited from acamprosate in that they were more likely to abstain from heavy drinking during the past 2 months of treatment. 18 In that same investigation, very frequent drinkers also benefited from the medication naltrexone in that they were more likely to be continuously abstinent.…”
mentioning
confidence: 99%
“…Raittiustavoitteeseen päätyneiden on todettu py syvän raittiina tai ainakin kohtuudessa paremmin kuin muunlaisen tavoitteen valinneet (19)(20)(21)(22). Tässä tutkimuksessa enemmistö tutkittavista valitsi alussa raittiustavoitteen.…”
Section: Pohdintaunclassified
“…Tässä tutkimuksessa enemmistö tutkittavista valitsi alussa raittiustavoitteen. Vaikka vain kol mannes heistä säilytti raittiustavoitteen koko seurannan ajan, niin heillä oli aikaisempien tutki musten (19)(20)(21)(22) tavoin vähemmän runsasta alko holin käyttöä ja enemmän raittiutta kuin vähen tämisen tavoitteekseen valinneilla.. Terveys on tärkeä koettu syy alkoholin käytön lopettamiselle (1)(2)(3)(4)(5)(6). Tässä tutkimuksessa monet riippumatta alun tavoitteesta olivat raittiina useita kuukausia sairastumisen jälkeen ja uudelleen sairastumisen pelko näytti useilla hillitsevän alkoholin käyttöä myös pitkällä aikavälillä.…”
Section: Pohdintaunclassified